Synthesis and performance of a Mono (dodecafluoroheptyl) acetate surfactant. Issue 3 (4th March 2019) - Zhai, Congcong; Zhang, Luqing; Azhar, Umair; Zong, Chuanyong; Xu, Anhou; Zhang, Shuxiang; Zhang, Yabin
Abstract: A novel fluorinated surfactant, sodium 1 H, 1 H, 7H-dodecafluoro-1-heptyloxy acetate (DFHAS), was synthesized via a facile two-step synthetic procedure. The structure of product on each step was characterized by 1  H NMR, 19  F NMR, 13 C NMR, FT-IR, and mass spectrum (MS). Ultraviolet absorption (UV) and ring measurements were performed to obtain detailed information of its surface properties. The results demonstrated that the novel surfactant possessed very low critical micelle concentration (CMC, 7.94 mM) and surface tension (20.01 mN/m). Furthermore, the surfactant had preferable thermal stability compared with other perfluorocarboxylates characterized by thermal gravimetric analysis (TGA). The practical application performance of DFHAS was finally validated through the emulsion polymerization of vinylidene fluoride (VDF) by means of its excellent emulsifying activities. It is expected that this versatile synthetic strategy may help fabricate satisfying green surfactant systems for the application in fields of emulsion polymerization, drug delivery and greases.GRAPHICAL ABSTRACT